A study on microbiology culture of acute appendicectomy specimen and its correlation with wound infection - Parthiban, N.; Harish, Mamilla (International Surgery Journal, 2017)
Background: Appendicitis is a common condition which frequently requires emergency surgery and has postoperative wound infection has been reported in few cases which can be influenced by many factors, the most important being surgical skill and technique and the criteria used to define the infection. Bacteria play an important role in appendicitis and the local application of antibiotics or antiseptics can reduce the incidence of wound infection. In this study, we analyse the microbiology culture of acute appendicectomy specimen and its correlation with wound infection. Methods: This is a randomised control test study which was carried out 56 patients with appendicitis. The swab was taken from appendix lumen after appendicectomy and wound infection was sent to laboratory to carry out histology findings and infective organisms respectively. All patients were followed postoperatively for wound infection. Results: Bacteria was isolated from 60% swabs taken from appendix lumen in which gram-negative bacilli isolated as commonest bacteria among which perforated appendicitis shows 66.7% isolation of bacteria. Wound infection among patients underwent appendicectomy was 21%. Gram-negative bacilli were isolated from almost all swabs (100%) taken from wound infection. Conclusions: From this study and results, it shows gram negative bacilli was the commonest organisms isolated from the swabs taken from both appendix lumen and wound infection.